AKTUALISASI KEBUDAYAAN DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SMAN 3 CIBINONG - Zahratu, Nazwa Salsabila; Putri, Kayla Fellicia; Lestari, Hera Aprillya Dwi; Syahladin, Firny Ramadhina; Sitanggan, Febriola (LPPM Institut Pendidikan Nusantara Global, 2023)
This article discusses the Actualization of Culture in the Implementation of the Independent Curriculum at Senior High School 3 Cibinong which focuses on implementing the Independent Curriculum, as well as involving culture in the curriculum. Central government policy in increasing the role of culture in the education system, especially in the West Java region. This research uses qualitative data with data collection techniques in this research using interviews and literature studies. The researchers collected data through primary and secondary data sources, namely: Interviews conducted with those in the curriculum, guidance and counseling (BK), teaching teachers and student representatives from each generation at SMA Negeri 3 Cibinong. Data was obtained by searching and reviewing various information by reading journals, books and various other literary sources. The aim of this research is to find out how this government policy is implemented in achieving the goals of freedom to learn and freedom of culture. The Merdeka Curriculum is interpreted as a learning design that provides students with the opportunity to study calmly, relaxed, fun, stress-free and pressure-free to show their natural talents. The cultural implementation of the Independent Curriculum can be applied to local content based on regional characteristics and local wisdom. Cultural implementation can be obtained in terms of student learning at school, for example regional specialties, traditional dances and drama from Sunda, West Java.